(untitled) (Global Journal of Human-Social Science, 2017)
This paper develops a three-sector theoretical growth model to capture the role of consumers’ acceptance towards the second generation of genetically modified (GM) crops in the long run growth process of the economy. An Acceptance (towards GM crop) parameter is defined as a ratio of consumption of GM to traditional variety of food, whose growth rate is determined by growth rate of human capital. Dynamic stability of the system is ensured provided the value of acceptance parameter is within a certain range. A range of the acceptance parameter is also obtained which ensures not only the dynamic stability of the system but also ensures higher rate of growth of an economy that produces both GM and non-GM crops compared to an economy that does not produce GM crops. The empirical validation of the model through panel data analysis suggests that research and development activity in agriculture is key to the growth process of the economy as it helps to form acceptance towards new technology among consumers.